Cobalt(II) chloride complexes with some phosphine oxides: compatibility between structural data for the solid complexes and their stability constants in acetone medium - Massabni, Antonio Carlos; Bladimiros Melios, Cristo (Eclética Química, 2019)
Binary complexes of general formula CoCl2L2, where L = triphenylphosphine oxide (TPPO), benzyldiphenylphosphine oxide (BDPPO), dibenzylphenylphosphine oxide (DBPPO) and tribenzylphosphine oxide (TBPO) were considered concerning X-ray structural data for the complexes in the solid state and their stability constants in acetone solution. Compatibility between structural data and stability constants are pointed out. Previous investigations showed that in acetone medium, with CoCl2 as reference acceptor, the following basicity order is obeyed: TBPO > DBPPO > BDPPO > TPPO. This sequence is supported by X-ray diffraction data of the solid complexes and by electrolytic conductance values for these complexes both in acetone and in nitromethane media.